Optimal Treatments for Severe Malaria and the Threat Posed by Artemisinin Resistance. (5th December 2018) - Jones, Sam; Hodel, Eva Maria; Sharma, Raman; Kay, Katherine; Hastings, Ian M
Abstract: Background: Standard treatment for severe malaria is with artesunate; patient survival in the 24 hours immediately posttreatment is the key objective. Clinical trials use clearance rates of circulating parasites as their clinical outcome, but the pathology of severe malaria is attributed primarily to noncirculating, sequestered, parasites, so there is a disconnect between existing clinical metrics and objectives. Methods: We extend existing pharmacokinetic/pharmacodynamic modeling methods to simulate the treatment of 10000 patients with severe malaria and track the pathology caused by sequestered parasites. Results: Our model recovered the clinical outcomes of existing studies (based on circulating parasites) and showed a "simplified" artesunate regimen was noninferior to the existing World Health Organization regimen across the patient population but resulted in worse outcomes in a subgroup of patients with infections clustered in early stages of the parasite life cycle. This same group of patients were extremely vulnerable to resistance emerging in parasite early ring stages. Conclusions: We quantify patient outcomes in a manner appropriate for severe malaria with a flexible framework that allows future researchers to implement their beliefs about underlying pathology. We highlight with some urgency the threat posed to treatment of severe malaria by artemisinin resistance in parasite early ring stages. Abstract : A new mathematical model of severe malaria calculating pathology of sequestered parasites shows the standard World Health Organization regimen outperforms a simplified artesunate regimen in patients with early stage synchronized infections. Artesunate resistance leads to worse outcomes for these patients.